Adopsi Ekonomi Sirkular Menuju ‘Zero Poverty’ di Desa Margamukti Kabupaten Sumedang - Atih Rohaeti Dariah; Hilwati Hindersah; M. Samsuri; A. Harits Nu’man; Darman Puja Kurniawan; Neng Dewi Himayasari; Nadya Safitri (UNISBA Press, 2024)
Abstract. English translation. The circular economy has become a business model trend in responding to environmental problems and towards sustainable business. Community service activities are carried out in Margamukti Village, Sumedang Regency by carrying out the concept of circular economy. The typology of Margamukti Village area located on the outskirts of the capital city of Sumedang, is rice fields where the function of space is dominated for agricultural land. The Margamukti Village Government has tried to adopt the circular economy concept contained in the Margamukti Village Circular Economy Innovation Profile document. This article will discuss how the adoption of a circular economy that can optimize the potential of the leading economy while creating employment opportunities and reducing poverty, which will be outlined in a more structured plan document and put forward a buttom-up approach. There are four methods in this activity, namely, content analysis, deductive method, focus group discussion, and mentoring process. Some analysis of the results of activities includes proposals to identify the entrepreneurial potential of farmer groups. In the profile document, there is also no monitoring of evaluation, no duration of time and no achievement indicators. This means that profile documents need to be refined by accommodating all findings from the results of this service into a roadmap. Abstrak. Ekonomi sirkular telah menjadi trend model bisnis dalam merespon masalah lingkungan hidup dan menuju bisnis berkelanjutan. Kegiatan pengabdian dilaksanakan di Desa Margamukti Kabupaten Sumedang dengan mengusung konsep ekonomi sirkular. Tipologi wilayah Desa Margamukti yang terletak di pinggiran Ibu Kota Sumedang adalah persawahan dimana fungsi ruang didominasi untuk lahan pertanian. Pemerintah Desa Margamukti sudah mencoba mengadopsi konsep ekonomi sirkular yang tertuang dalam dokumen Profil Inovasi Sirkular Ekonomi Desa Margamukti. Artikel ini akan membahas bagaimana adopsi ekonomi sirkular yang dapat mengoptimalkan potensi ekonomi unggulan sekaligus menciptakan kesempatan kerja dan menurunkan kemiskinan, yang akan dituangkan dalam dokumen rencana yang lebih terstruktur dan mengedepankan pendekatan buttom-up. Terdapat empat metode dalam kegiatan ini yakni, content analysis, metode deduktif, diskusi kelompok terfokus, dan proses pendampingan. Beberapa analisis hasil kegiatan antara lain berupa usulan untuk identifikasi potensi kewirausahaan kelompok peternak. Dalam dokumen profil juga tidak terdapat bagaimana monitoring evaluasi, tidak ada durasi waktu dan tidak ada indikator capaian. Artinya dokumen profil perlu disempurnakan dengan mengakomodir seluruh temuan dari hasil pengabdian ini ke dalam sebuah roadmap.